MENINGKATKAN PENDIDIKAN MELALUI UNITED NATIONS ORGANIZATION DAN HAK ASASI PENDIDIKAN - Hartana; I Gede Yoga Esa Mahendra (Universitas Pendidikan Ganesha, 2020)
Rights exercised in different educational systems and different learning settings constitute a human rights-based understanding of quality education. This study seeks to elucidate the goals and background of human rights education, national and international initiatives, and in particular the role of the United Nations in this regard. This study seeks to elucidate the goals and background of human rights education, national and international initiatives, and in particular the role of the United Nations in this regard. The method of conducting this research is the Literature Survey or Literature Survey method, and in this survey data collection activity is carried out by taking notes, reading activities and processing the survey data. UNESCO plays a central role in the design, implementation and evaluation of projects under the United Nations Decade of Action for Human Rights Education. This is done through the organization's many years of experience in teaching, human rights-based educational methods, and through the UNESCO network of schools, associations and educational institutions. Department of Human Rights and National Commissions. This international organization is responsible for promoting human rights education and is the principal organizer of the United Nations Decade of Human Rights.